Em Surdina (1933), de Lucia Miguel Pereira: um estudo sobre corpo e exílio - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
This work aims to develop a critical reflection on the novel Em Surdina (1933), by Lucia Miguel Pereira. The book brings in its plot the refusal of the protagonist Cecília to surrender to the destiny reserved for the majority of women of her time and social class: marriage. Therefore, from the in-depth reading of the story, we analyze the literary strategies used by a female author to build a critical reflection on the social role that women played in society in the 1930s. At first, the research is concerned with issues of contextualization, biographical and ideological, as well as the construction of a path of Brazilian feminist thought, using the theoretical assumptions of Feminist Criticism. Then, the reflection turns to the theme of the meaning of the body. Based on the theoretical assumptions of Elizabeth Grosz (2000) and Jean Luc Nancy (1996 - 2000), we think about the female body and the compression of all its meanings in only one way. Still, according to Nancy (2000), we seek to understand Exile as existence and writing and literature as a way of touching this marginalized body.
Keywords: Corpo; Crítica Feminista; Exílio; Body; Exile; Feminist Criticism; CNPQ::LINGUISTICA, LETRAS E ARTES